Oriental Republic of Uruguay : Country Financial Accountability Assessment - World Bank (Washington, DC, 2012)
The Country Financial Accountability Assessment (CFAA) for Uruguay analyzes two principal roles: (1) to identify the strengths and weaknesses of Public Financial Management (PFM) arrangements in Uruguay, and (2) to contribute to the strengthening of Uruguay's economic governance and associated social and economic development by identifying weaknesses and recommending remedial action in areas where current cumbersome systems contribute to poor public sector management. Some of the recommendations are: National Budgets should include all government entities performing non-commercial activities. The annual budgets and financial statements of autonomous commercial and industrial entities should be presented to the Parliament at the same time as the National Budget. In order to improve capacity for performance budgeting, analytical and cost accounting in the Government, a comprehensive management and budgeting capacity building program should be designed and implemented. The integrated financial information system (SIIF) Budget Evaluation Module (SEV) should be fully implemented, and a framework for analysis of efficiency and effectiveness of resource utilization created. Financial accounting and reporting practices should be expanded. Priority should be given to developing and implementing the SIC accounting module of SIIF. In order to promote a uniform control environment, internal audit units of staff reporting directly to the ministries and autonomous entities should be developed.